2015
DOI: 10.1016/j.lssr.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined exposure to protons and 56 Fe leads to overexpression of Il13 and reactivation of repetitive elements in the mouse lung

Abstract: Interest in deep space exploration underlines the needs to investigate the effects of exposure to combined sources of space radiation. The lung is a target organ for radiation, and exposure to protons and heavy ions as radiation sources may lead to the development of degenerative disease and cancer. In this study, we evaluated the pro-fibrotic and epigenetic effects of exposure to protons (150 MeV/nucleon, 0.1 Gy) and heavy iron ions (56Fe, 600 MeV/nucleon, 0.5 Gy) alone or in combination (protons on Day 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These results suggest that, even though not visible in our protein readouts, proton exposure primed the cardiac tissue by inducing certain defense mechanisms that diminished the cardiac response to a subsequent challenge. Similar to our results, recent work on tissue samples of lung [34] and brain (Antiño Allen, PhD, personal communication) of mouse models showed that protons followed at 24 hours by 56 Fe resulted in molecular and functional alterations that were significantly different when compared to either source of radiation alone. Moreover, in mice that were challenged with an acute myocardial infarction, prior proton irradiation increased the expression of pro-survival genes, improved the restoration of cardiac function, and enhanced the process of cardiac remodeling when examined from hours to months after irradiation [13].…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that, even though not visible in our protein readouts, proton exposure primed the cardiac tissue by inducing certain defense mechanisms that diminished the cardiac response to a subsequent challenge. Similar to our results, recent work on tissue samples of lung [34] and brain (Antiño Allen, PhD, personal communication) of mouse models showed that protons followed at 24 hours by 56 Fe resulted in molecular and functional alterations that were significantly different when compared to either source of radiation alone. Moreover, in mice that were challenged with an acute myocardial infarction, prior proton irradiation increased the expression of pro-survival genes, improved the restoration of cardiac function, and enhanced the process of cardiac remodeling when examined from hours to months after irradiation [13].…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study, we reported a lack of repetitive elements-associated changes in DNA methylation in mice four weeks after exposure to low absorbed mean doses of protons, 56 Fe or sequential exposure to protons and 56 Fe (Nzabarushimana et al, 2015). Analysis of LINE-1 DNA methylation in that study, similar to the vast majority of other studies, was performed on the LINE-1 ORF1.…”
Section: Discussionmentioning
confidence: 96%
“…The role of epigenetic alterations, including aberrant methylation and expression of LINE-1 elements in the development and promotion of radiation-induced fibrosis and lung cancer is becoming increasingly recognized (Ikeda et al, 2013; Saito et al, 2010; Weigel et al, 2015). In our previous studies, we reported the long-term dose-dependent genomic and LINE-1 ORF1-associated DNA hypermethylation in the mouse lung 5 months after exposure to heavy iron ions ( 56 Fe) (Nzabarushimana et al, 2014), but failed to identify changes in LINE-1 ORF1 methylation four weeks after exposure to either protons or 56 Fe exposure, or as a result of the sequential exposure to both (Nzabarushimana et al, 2015). In this study, we aimed to investigate whether or not exposure to environmentally relevant low absorbed mean doses of densely IR would result in evolutionary- and family-dependent alterations in the DNA methylation status of LINE-1 in the mouse lung.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that alterations in DNA methylation is the general feature of space radiation and that these alterations are primary attributable to repetitive elements. Indeed, exposures to low absorbed mean doses of protons and 56 Fe ions relevant to the space environment lead to significant alterations in DNA methylation and expression of repetitive elements in the bone marrow, liver and lung tissues [1417]. As these changes in repetitive elements may persist for a long time post exposure, this suggests their potentially causative role in radiation-induced late tissue damage and disease development and progression.…”
Section: Introductionmentioning
confidence: 99%